Dialektika Norma Islam dan Norma Hukum Positif dalam Pembentukan Peraturan Daerah tentang Pendidikan Al-Qur’an di Provinsi Gorontalo - Rahmat Teguh Santoso Gobel; Moh. Ihsan Husnan; Novendri Nggilu; Raihan Sahrul Adnan; Moh. Hidayat Muhtar (Sultan Jurisprudence: Jurnal Riset Ilmu Hukum, 2022)
This article discusses the problems of regulating Koranic education in regional regulations in Gorontalo Province. This is based on the consideration of the Ministry of Home Affairs which states that the draft regional regulation on Koranic education cannot be regulated separately but is integrated with existing regional regulations for the provision of education. These problems will be answered methodologically by using normative legal research. The author uses this legal research because the focus is on reviewing literature studies, laws and regulations and court decisions related to the object of research.   Based on the results of the study, this article concludes that the establishment of a regional regulation in the Gorontalo province regarding Qur'anic Education has the potential to cause conflict with the principles of establishing legislation. This is based on the material content of regional regulations that require protection for all groups and religions to prevent discriminatory actions on the formation of a regional regulation.The basis for regulating Qur'anic education should be used as part of local wisdom where the province of Gorontalo is known as the Serambi Medina area with a majority Muslim population supported by a strong culture so that a legal policy for the Gorontalo Provincial government is needed to accommodate Qur'anic education in regional regulations regarding the implementation of education in the region so that later the values of the Koran are not only accepted in the sociological scope but are recognized juridically.   Therefore, it is necessary to revise regional regulations on the implementation of education by including a chapter on religious education which does not only regulate Koranic education, but other religions can also be included in the chapter. If the regional regulations have been revised, the next effort is to strengthen Koranic education, it is necessary to make an implementing regulation, namely the governor's regulation on Koranic education as a follow-up to regional regulations on the implementation of education..